(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Subclinical hypothyroidism (SCH) is one of the most common thyroid dysfunctions observed in patients with Type 2 Diabetes Mellitus and may adversely affect glycemic control and cardiovascular risk. The coexistence of diabetes mellitus and thyroid dysfunction contributes significantly to metabolic disturbances and diabetic complications. This study aimed to determine the prevalence and association of SCH among adult patients with type 2 diabetes mellitus in a tertiary care hospital. Methodology: This analytical cross-sectional study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from March 2025 to November 2025. A total of 300 adult patients with type 2 diabetes mellitus were included using convenient sampling technique. Clinical evaluation and laboratory investigations including fasting blood sugar, HbA1c, lipid profile, serum TSH, free T3, and free T4 were performed. SCH was defined as elevated TSH levels with normal free T3 and free T4 levels. Statistical analysis was performed using SPSS version 25.0 with p <0.05 considered statistically significant. Results: The prevalence of SCH among diabetic patients was 16%. SCH was significantly more common among females compared to males (p=0.02). Patients with SCH had significantly higher HbA1c and total cholesterol levels compared to euthyroid patients. Multiple logistic regression analysis demonstrated increased odds of SCH among patients with poor glycemic control. Conclusion: Subclinical hypothyroidism is prevalent among patients with type 2 diabetes mellitus and is associated with poor glycemic control and dyslipidemia. Routine thyroid screening may aid in early diagnosis and improved metabolic management.